Charge doping into spin minority states mediates doubling of T C in ferromagnetic CrGeTe3 - Liam Trzaska; Lei Qiao; Matthew D. Watson; Monica Ciomaga Hatnean; Igor Marković; Edgar Abarca Morales; Tommaso Antonelli; Cephise Cacho; Geetha Balakrishnan; Wei Ren; Silvia Picozzi; Phil D. C. King (npj 2D Materials and Applications)
Abstract The recent discovery of the persistence of long-range magnetic order when van der Waals magnets are thinned towards monolayers provides a tunable platform for engineering of novel magnetic structures and devices. Here, we study the evolution of the electronic structure of CrGeTe3 as a function of surface electron doping. From angle-resolved photoemission, we observe spectroscopic fingerprints that this electron doping drives a marked increase in T C, reaching values more than double that of the undoped material, in agreement with recent studies using electrostatic gating. Together with density functional theory calculations and Monte Carlo simulations, we show that, surprisingly, the increased T C is mediated by the population of spin-minority Cr t 2g states, forming a half-metallic 2D electron gas. This promotes a novel variant of double exchange, and unlocks a significant influence of Ge – which was previously thought to be electronically inert in this system – in mediating Cr-Cr exchange.